Accounting for intangible assets : a conceptual framework for measurement and reporting on intangible assets - Wyatt, Anne.; Abernathy, Margaret A.; Intellectual Property Research Institute of Australia (Melbourne, Vic. : The Institute, 2003)
Accounting regulators are grappling with the trade-offs between the relevance of external financial reports and maintaining the reliability and verifiability of the information provided. The question is how to incorporate more financial information abount intagibles into the external financial reporting, and the internal systems, without reducing the usefulness of the data due to measurement error. This paper address that question by developing a coherent framework for the classification, recognition and reporting of intangible assets that is based on sound economic principles.
1. Introduction -- 2. Reporting of intangible assets within existing regulatory frameworks -- 3. A consistent framework for comparable classification, recognition and reporting of intagibles -- 4. The reporting framework -- 5. Discussion and summary -- References.
"December 2003"
Includes bibliographical references (p. 28-32)
Also available online via the World Wide Web at http://www.ipria.org/.
Keywords: Intangible property -- Accounting; Intangible property -- Measurement